Minimum Core and the Right to Education - Fisher, Angelina (World Bank, Washington, DC, 2018)
Minimum core is a concept introduced by the Committee on Economic, Social and Cultural Rights (“Committee”) with the aim of ensuring “the satisfaction of, at the very least, minimum essential levels of each of the rights is incumbent upon every State party.” The minimum core concept aims to set a quantitative and qualitative floor of socio-economic and cultural rights that must be immediately realized by the state as a matter of top priority. The promise of the minimum core approach is “to give the notion of progressive realization a clearer direction and to evaluate the steps states have taken towards the progressive realization of particular rights”. Yet, the Committee itself has been inconsistent in defining the content and scope of the “minimum core” concept for different rights. Although the original definition—focused on minimum essential levels—seems narrowly constructed, in more recent General Comments, the Committee has given the “minimum core” a far more expansive interpretation.Further complicating the query is the fact thatstates rarely use “minimum core” terminology in State Reports to the Committee. Where national courts have referred to the “minimum core” concept—a rare reference—their interpretation has not always been consistent with that of the Committee. In academic literature, too, disagreements remain about the content, scope and even utility of the “minimum core” concept. Without taking a position on which interpretation of the “minimum core” is normatively desirable, this paper aims to provide a descriptive account of how different actors define the content and scope of “minimum core” of the right to education.The paper begins by providing a summary of academic engagement with the concept of “minimum core”, highlighting different features of the concept that have been identified in the literature. In Part two, the paper examines how the concept of “minimum core” is featured in the international legal framework. In Part three, the paper considers whether, and if so how, the concept of “minimum core” features in national laws and jurisprudence by sampling a few states. In Part four, the paper discusses the use of indicators and other quantitative measures in relation to the content of “minimum core”. The paper concludes by suggesting how development banks might use the concept of “minimum core” to guide their work.